Anchoring and adjustment as a moderator on the impact of computerised order entry on clinical efficiency. (2nd August 2019) - McCreless, Tamuchin
Studies on the effectiveness of clinical decision support systems on impacting clinical outcomes have shown varying results. A gap exists in understanding the factors that play a role in the relationship between the decision support systems, providers, and clinical outcomes. This study explores the role of adjustment level, or the difference between a clinician's initial evaluation of a treatment path for a patient, and the treatment path presented by a decision support system. The study suggests that where the adjustment level is high, decision support systems are not as effective in affecting outcomes than when adjustment levels are low.